Perbandingan Efektivitas Kombinasi OHO (Obat Hipoglikemik Oral) Terhadap Gula Darah Puasa Pasien Diabetes Melitus Tipe 2 Comparison of the Effectiveness of Oral Hypoglycemic Agents (OHO) on Fasting Blood Glucose Levels in Type 2 Diabetes Mellitus Patients - Talitha Elliora Salsabilla; Zulfachmi Wahab; Yanuarita Tursinawati (KOLONI, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease characterized by insulin resistance and impaired insulin secretion, leading to increased blood glucose levels. Optimal blood glucose control is necessary to prevent long-term complications. One of the parameters used to assess glycemic control is Fasting Blood Glucose (FBS). This study aims to compare the effectiveness of the combination of metformin-glimepiride and metformin-gliclazide on FBS levels in T2DM patients. This study is a quantitative, observational, and analytical study using a cross-sectional approach. Data were obtained from the medical records of outpatients with T2DM at K.R.M.T. Wongsonegoro Regional General Hospital from January 2022 to December 2023. The study sample consisted of 50 patients selected using a purposive sampling technique, consisting of 25 patients receiving metformin-glimepiride therapy and 25 patients receiving metformin-gliclazide therapy. Data analysis was performed using the Paired T-Test, Mann–Whitney, and Independent T-Test. The results showed that both therapy combinations resulted in significant reductions in GDP after three months of therapy. The Mann–Whitney test showed no significant difference in GDP reduction between the two groups. However, the Independent T-Test showed a significant difference in final GDP levels, with the metformin-gliclazide group having a lower mean final GDP than the metformin-glimepiride group. Therefore, the metformin-gliclazide combination is superior in controlling GDP levels in patients with type 2 diabetes compared to the metformin-glimepiride combination.